2001
DOI: 10.1046/j.1365-2362.2001.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

LEPR gene polymorphisms: associations with overweight, fat mass and response to diet in women

Abstract: In women, genetic variations at the LEPR gene level are associated with overweight and fat mass in a cross sectional study and with response to low calorie diet in an intervention study. These results indicate that variations at the leptin receptor locus are associated with common obesity phenotypes and are a part of the polygenic influences on the response to nutritional environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 44 publications
2
38
0
6
Order By: Relevance
“…Previous studies illustrated that the association between Ser343Ser and obesity are controversial among different ethical populations. Our results were in agreement with the finding of (Mammes et al 2001). Similarly, our finding was in accordance with that obtained by (Okada et al 2010)who found that rs1805134 CC showed a significant association with low level of triglyceride.…”
Section: Discussion:-supporting
confidence: 94%
“…Previous studies illustrated that the association between Ser343Ser and obesity are controversial among different ethical populations. Our results were in agreement with the finding of (Mammes et al 2001). Similarly, our finding was in accordance with that obtained by (Okada et al 2010)who found that rs1805134 CC showed a significant association with low level of triglyceride.…”
Section: Discussion:-supporting
confidence: 94%
“…21 Two other SNPs, Ser343Ser (rs790419) in exon 1 and Lys109arg (rs1137100) in exon 4 of the LEPR gene, have been associated with obesity in women in France. 22 To obtain a better understanding of the association between leptin and colon cancer, we evaluated 2 variants of the LEP gene, the more commonly studied rs7799039 as well as rs2167270 and 1 variant of the LEPR gene, rs6588147 with risk of developing colon cancer. These variants were selected because of previous reports of their reported functional importance 23 and their being in linkage disequilibrium with other common LEP markers such as rs2167270 and rs3828942.…”
mentioning
confidence: 99%
“…Furthermore, carriers of a variant C allele in the LEPR gene [Ser (T) 343Ser (C)] have lost more weight in response to a low calorie intake than the noncarriers (26).…”
Section: Genetic Aspect Of Obesitymentioning
confidence: 99%